Measuring the dimensions of flexible driving among the heads of sports clubs from the point of view of coaches (Journal of the College of Basic Education, 2022)
The current research seeks to identify the measurement of the dimensions of flexible driving among the heads of sports clubs from the point of view of coaches. In order to achieve the goals of the current research, the researcher followed the steps of the descriptive approach, which began with a clear definition of the research community and its sample in addition to the research tool. The researcher identified the research community with all the trainers working in Iraqi sports clubs. As for the research sample, it included (150) trainers and trainers from (10) different Iraqi clubs. As for the research tool, which is (flexible driving questionnaire), the researcher built the questionnaire and presented it to a group of experts and arbitrators in order to arbitrate it. After extracting the psychometric properties of the current research tool and reassuring its validity in the application, it was applied to the research sample and the following results were reached:Based on the above, the following is evident:1. The managers and heads of Iraqi clubs in the mentioned sample possess the characteristics of flexible leadership in facilitating the affairs of the club 2.The flexible leader has the qualities of working hard in dealing with coaches and workers at the club 3.Managers and club heads possess a set of skills in managing their human relationships with those around them.